'Seeing' our tamariki in longitudinal studies: exploring the complexity of ethnic identification trajectories within Growing Up in New Zealand. Issue 3 (27th May 2022) - Atatoa Carr, Polly; Langridge, Fiona; Neumann, Denise; Paine, Sarah-Jane; Liang, Renee; Taufa, Seini; Fa'alili Fidow, Jacinta; Fenaughty, John; Kingi, Te Kani
ABSTRACT: Longitudinal research provides unique opportunities for ethnic identification research and for understanding ethnic identity development. However, ethnic identification is subjective, fluid, multi-dimensional, and context-specific. This study draws on Growing Up in New Zealand longitudinal data to explore: how children identify their ethnicity/culture; and how these descriptions compare with ethnic identification patterns described by their parent. At eight years of age children described their ethnicity/culture as Pākehā/New Zealand European (52%); Māori (22%); Samoan (8%); Tongan (5%); Cook Islands (4%); Chinese (4%); Indian (5%); Niuean (2%); Australian (4%); and 14% said they don't think about their ethnicity. Across time, approximately 60% of the cohort have always been identified as or identified themselves as European, Māori and Asian respectively and 72% had always been identified as (or identified themselves) as Pacific. These findings show that emerging ethnic identification is complex, and differs according to who is responding and when, as well as according to ethnic identification itself. Measuring and interpreting ethnicity is an important opportunity for longitudinal studies . However, given the fluidity and contingency of this data, researchers face ongoing challenges in: maintaining kaitiakitanga (stewardship); providing robust evidence to guide policies that enhance wellbeing equity; and upholding Treaty of Waitangi obligations.